The Effect of Overexposure to Blue Light from Digital Screens before Bed on Children’s Sleep and Bruxism in Ages 6–12 - Khames T. Alzahrani, (Asian Journal of Pharmaceutics (AJP), 2026)
Introduction: Exposure to blue light from digital screens at bedtime may suppress melatonin production and disrupt circadian rhythms, potentially affecting sleep quality. Bruxism, a parafunctional habit involving teeth grinding, is often linked to stress and sleep disturbances. In children, it may result in tooth wear, jaw discomfort, and poor sleep, raising questions about its association with bedtime screen use. Objectives: This study investigates the relationship between bedtime blue light exposure, sleep quality, and pediatric sleep bruxism (SB) in Saudi children. Methodology: This cross-sectional study was conducted across Saudi Arabia to examine the association between pre-bedtime blue light exposure and the occurrence of sleep disturbances and bruxism in children aged 6–12 years. Data were obtained using a three-part structured questionnaire, adapted from a validated instrument, and distributed to parents via social media platforms. The Arabic-language questionnaire collected information on demographics, screen use patterns, bedtime routines, and bruxism-related symptoms. Sleep-related variables were assessed through 24 statements rated on a 4-point Likert scale, yielding a maximum score of 72 points, with sleep disturbance severity classified as low, moderate, or high according to Bloom’s cut-off points. In addition, four open-ended questions explored qualitative aspects of children’s sleep patterns, and responses were subjected to descriptive analysis.